Incorporating Robsons classification in analysis of caesarean section at rural territory centre for 18 months - Santhi, Vege V.; Gogineni, Sajana; Sunita, C.; Mahathi Panchumarthi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: With the rise of caesarean sections (CS) over the last five decades, World Health Organization (WHO) proposed that health care facilities to use the Robsons 10 group classification system to audit their caesarean sections rates. This classification would help understand internal structure of the CS rates at individual health facilities identify population groups, indication in each group and formulate strategies to reduce these rates. Methods: This is a retrospective study for a period of 18 months at tertiary care hospital in rural area at department of obstetrics and gynaecology, Dr. PSIMS & RF, Chinnoutpalli, Vijayawada, Andhra Pradesh. Women who delivered during this period were analysed and classified into Robsons group 10 classification and percentages were calculated for the overall rate, the representation of groups, contribution of groups and caesarean percentage in each group in rural territory centre during the period of January 2021 to June 2022. Results: From January 2021 to June 2022 there were total of 547 deliveries. Out of which 224 had caesarean section accounting for a caesarean delivery rate of 40.9%. When data was analysed according to Robsons 10 group classification maximum contribution of caesarean section was with Robsons group 5.1 (36%), which comprised of patients with term cephalic multiparous with one previous scar. Followed by group 2A (21%), which comprised of patients with term cephalic nulliparous with labour induced. Breech pregnancies are completely undergoing caesarean section (groups 6 and 7). Conclusions: We identified the contribution of each group to the overall CS rate as well as the CS rate within each group. Women with previous caesarean delivery contribute to the increasing proportion of caesarean deliveries. Use of Robson criteria allows standardized comparisons of data and identifies clinical scenarios in caesarean rates. All institutes to audit themselves to evaluate quality of caesarean section rates and to rationalize caesarean rates. Impact of interventions to reduce caesarean rates should be studied and documented. Evaluation of existing management protocols and further studies into indications of CS and outcomes in our setting will helps us to design strategies and improve outcomes.